(untitled) (University Journal of Zoology, Rajshahi University, 2009)
The research work was conducted to measure the nursery pond water quality parameters during the period of June 2006 to May 2007 in Mymensingh. The highest value of water temperature, alkalinity, ammonia, free carbon dioxide, DO, PH and hardness was 30.2Â°C (May’07) in pond-1, 174ppm (Feb.’07) in pond-2, 3.5ppm (July’06) in pond-1, 8.5ppm (Dec.’06&Jan.’07) in pond-1, 9ppm (July;06) in pond-1(also in April in pond-2), 8.4 (June’06) in pond-2 and 175ppm (Sep.’06) in pond-2 respectively. The lowest value of these parameters was 18Â°C (Jan.’07) in pond-2, 70ppm (Nov.’06) in pond-1, 0.03ppm (Sep.’06) in pond-2, 4ppm (Sep.’06) in pond-2, 5.5ppm (June’06) in pond-1, 6.2 (Oct.’06) in pond-2 and 64ppm (March’07) in pond-1. The value of physicochemical parameters of water had more or less significant combined effect on one another. Key words: Physicochemical, nursery pond, fish fry, disease Â doi:10.3329/ujzru.v27i0.1952 Univ. j. zool. Rajshahi Univ. Vol. 27, 2008 pp. 43-46